2021
DOI: 10.3390/ijms22063189
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CaMKII and ERK Signaling in Addiction

Abstract: Nicotine is the predominant addictive compound of tobacco and causes the acquisition of dependence through its interactions with nicotinic acetylcholine receptors and various neurotransmitter releases in the central nervous system. The Ca2+/calmodulin-dependent protein kinase II (CaMKII) and extracellular signal-regulated kinase (ERK) play a pivotal role in synaptic plasticity in the hippocampus. CaMKII is involved in long-term potentiation induction, which underlies the consolidation of learning and memory; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 171 publications
0
22
0
Order By: Relevance
“…To further elucidate the downstream intracellular pathways involved in the effects of CB1R blockade, we used immunoblotting to study the expression of ERK and phosphorylated ERK (p-ERK), key regulators of synaptic plasticity [ 27 ]. In addition, activation of CB1R triggers mammalian target of rapamycin (mTOR) signalling in the hippocampus [ 28 ]; we quantified phosphorylated (active) mTOR in both saline- and cocaine-treated mice.…”
Section: Resultsmentioning
confidence: 99%
“…To further elucidate the downstream intracellular pathways involved in the effects of CB1R blockade, we used immunoblotting to study the expression of ERK and phosphorylated ERK (p-ERK), key regulators of synaptic plasticity [ 27 ]. In addition, activation of CB1R triggers mammalian target of rapamycin (mTOR) signalling in the hippocampus [ 28 ]; we quantified phosphorylated (active) mTOR in both saline- and cocaine-treated mice.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, our data suggest that the inhibitory effect of U0126 depends on the BLA, which is consistent with Wells et al ( 2013 ) study that ERK in the BLA is critical for context-response–cocaine reconsolidation (Wells et al, 2013 ). Consolidation of new drug-related memories is ERK dependent (Lu et al, 2006 ; Jia et al, 2021 ). Similar findings have been reported that activation of the ERK pathway results in long-term changes in synaptic activity that underlie the consolidation of new memories (Schafe et al, 2000 ; Rodrigues et al, 2004 ; Feld et al, 2005 ; Lai et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“… Nicotine elicits the release of neurotransmitters such as norepinephrine, dopamine, acetylcholine, serotonin, glutamate, and GABA . It initiates its biological function by activating the nicotinic acetylcholine receptor through binding with ligand-gated ion channels Oxycodone is a highly selective full agonist of the MOR but has a low affinity for the δ-opioid and the κ-opioid receptors .…”
Section: Alkaloidsmentioning
confidence: 99%